After the Great Economic Collapse: Germany's Stimulus Package to Recover the Economy in Times of Covid-19 - Florian Dorn; Clemens Fuest; Florian Neumeier (CESifo Forum, 2020)
At the beginning of June 2020, the German government launched a comprehensive economic stimulus package to promote economic recovery. With a volume of EUR 130 billion, this program far outstrips programs launched in the wake of the financial and economic crisis of 2008/09. We present the fiscal policy measures adopted, show how companies assess various policies and finally discuss the most important elements of the economic stimulus package. The temporary reduction in VAT is one of the less convincing elements. On the other hand, those policy measures which promote medium- to long-term investments in future technologies, infrastructure, and climate protection are to be evaluated positively. Policies to stimulate demand cannot solve the problem of limited productivity due to protective restrictions or the collapse of international value-added chains in times of Covid-19. In this respect, one should not expect great impact on economic growth. Nevertheless, it makes sense to use fiscal policy measures to support the economy in these critical times.
Keywords: 330